Selective ex-vivo photothermal ablation of human pancreatic cancer with albumin functionalized multiwalled carbon nanotubes - Mocan L (Dove Medical Press, 2011)
Lucian Mocan1, Flaviu A Tabaran2, Teodora Mocan1, Constantin Bele3, Anamaria Ioana Orza1, Ciprian Lucan4, Rares Stiufiuc1, Ioana Manaila1, Ferencz Iulia1, Iancu Dana1, Florin Zaharie1, Gelu Osian1, Liviu Vlad1, Cornel Iancu11Department of Nanomedicine, “Iuliu Hatieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania; 2Department of Pathology, University of Agricultural Sciences and Veterinary Medicine, Cluj-Napoca, Romania; 3Department of Biochemistry, University of Agricultural Sciences and Veterinary Medicine, Cluj-Napoca, Romania; 4Clinical Institute of Urology and Renal Transplantation, Cluj-Napoca, RomaniaAbstract: The process of laser-mediated ablation of cancer cells marked with biofunctionalized carbon nanotubes is frequently called “nanophotothermolysis”. We herein present a method of selective nanophotothermolisys of pancreatic cancer (PC) using multiwalled carbon nanotubes (MWCNTs) functionalized with human serum albumin (HSA). With the purpose of testing the therapeutic value of these nanobioconjugates, we have developed an ex-vivo experimental platform. Surgically resected specimens from patients with PC were preserved in a cold medium and kept alive via intra-arterial perfusion. Additionally, the HSA-MWCNTs have been intra-arterially administered in the greater pancreatic artery under ultrasound guidance. Confocal and transmission electron microscopy combined with immunohistochemical staining have confirmed the selective accumulation of HSA-MWCNTs inside the human PC tissue. The external laser irradiation of the specimen has significantly produced extensive necrosis of the malign tissue after the intra-arterial administration of HSA-MWCNTs, without any harmful effects on the surrounding healthy parenchyma. We have obtained a selective photothermal ablation of the malign tissue based on the selective internalization of MWCNTs with HSA cargo inside the pancreatic adenocarcinoma after the ex-vivo intra-arterial perfusion.Keywords: noncovalent functionalization, irradiation, tumor, malignant, MWCNTs